2010
DOI: 10.1007/s12562-009-0206-x
|View full text |Cite
|
Sign up to set email alerts
|

Three types of proteinases in Japanese common squid Todarodes pacificus hepatopancreas as studied by using carp myofibrils as substrate

Abstract: Three types of proteinases, namely cystein-, metallo-, and serine-proteinases were found in squid hepatopancreas by studying the inhibition spectra using carp myofibril as substrates. Cystein-, metallo-, and serine-type showed the highest activities at 50 ºC, 35 ºC, and 40 ºC, respectively. The optimal pHs were pH 5, pH 7, and pH 9 for cystein-, metallo-, and serine-type, respectively. When assayed at 20 ºC and pH7.5, metallo-type showed the highest activity. Metallo-type was characterized by a high selectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The effect of the acid‐alkali treatment has also been reported in Tian's (Tian et al . ). The protein isolates, either acid or alkaline treatment, some degeneration occurs and there is an increase in the sensitivity to proteases, thus the pH‐shift process greatly improves the protein digestibility.…”
Section: Resultsmentioning
confidence: 97%
“…The effect of the acid‐alkali treatment has also been reported in Tian's (Tian et al . ). The protein isolates, either acid or alkaline treatment, some degeneration occurs and there is an increase in the sensitivity to proteases, thus the pH‐shift process greatly improves the protein digestibility.…”
Section: Resultsmentioning
confidence: 97%
“…This decrease of band intensity in the SV samples was likely caused by endogenous enzymes. Several previous studies revealed that squid contains endogenous proteolytic enzymes, including cathepsin L, metalloproteinases, cysteine proteinases, and serine protease [ 27 , 45 , 46 , 47 ]. Previous studies also demonstrated that endogenous enzymes such as cathepsin B and cathepsin L are involved in MHC, PM, and actin hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, excessively high temperature and a long setting time caused a reduction in gel breaking strength of acid-induced kamaboko gel. This decrease may be due to destruction of the gel matrix network, associated with the modori phenomenon [10] caused by cysteine protease [21]. Taking into consideration the breaking strength result only, the best setting condition would be 50°C for 6 h.…”
Section: Discussionmentioning
confidence: 99%